Exposure assessment of the population in Poland to the toxic effects of nickel from vegetable and their products - Monika Mania; Małgorzata Rebeniak; Jacek Postupolski (National Institute of Public Health - National Institute of Hygiene, 2019)
Background. According to the European Food Safety Authority (EFSA), vegetable and vegetable products can significantly contribute to dietary nickel intake. Consumption of vegetable across European Union can vary significantly and depends on consumption habits in individual Member States. Toxicity of Ni is dependent on the chemical form, the route of exposure and solubility of nickel compounds. Objectives. Determination of nickel content in commercially available vegetables and vegetable products and assessment of consumer exposure to Ni intake with these groups of foodstuffs. Materials and methods. 66 samples of vegetables and their products were analysed for nickel content. Nickel was determined after microwave mineralization of samples by atomic absorption spectrometry with a graphite furnace atomization (GFAAS). Nitric acid and perhydrol were used for the mineralization of the samples. The estimated exposure for adults and children was compared with the tolerable daily intake (TDI -Tolerable Daily Intake) set by the European Food Safety Authority at 2.8 μg /kg body weight (b.w.) per day. Results. Mean (MB-middle bound) Ni content from all investigated vegetable samples was 0.09 mg/kg (95th percentile MB 0.23 mg/kg). In vegetable products, mean Ni concentration was 0.191 mg/kg (95th percentile: 0.67 mg/kg). The highest nickel level was determined in the sample of roman lettuce (0.32 mg/kg), whereas lowest contamination was observed in the sample of onion (0.04 mg/kg). Contamination of investigated fruiting and leaf vegetable with nickel was slightly higher than root and bulb vegetables. The estimated average adults exposure to nickel from vegetable taking into account maximum absorption was 4.8% of TDI and 16.8% of TDI and does not pose a health risk. Exposure to nickel from vegetable products was 1.9% and 6.8% TDI, respectively. Conclusions. Obtained results demonstrate that dietary nickel intake from vegetables and their products do not constitute a significant health threat to consumers in Poland.